2008
DOI: 10.1007/s11708-008-0056-8
|View full text |Cite
|
Sign up to set email alerts
|

Aerodynamic performance of bowed compressor cascades with different camber angles

Abstract: The effects of a positively bowed blade on the aerodynamic performance of annular compressor cascades with different camber angles were experimentally investigated. The distributions of the exit total pressure loss and secondary flow vectors of the compressor cascades were analyzed. The static pressure was measured by tapping on the cascade surfaces, and the ink-trace flow visualizations were conducted. The results show that the value of the optimum bowed angle and optimum bowed height decrease because of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 4 publications
0
2
0
1
Order By: Relevance
“…При расчетах и исследованиях характеристик ступеней осевого компрессора в настоящее время используют аэродинамические характеристики компрессорных решеток, которые позволяют с достаточной степенью достоверности анализировать процессы, протекающие в лопаточных венцах ступеней осевого компрессора. В работе [9] приведены аэродинамические характеристики решеток, полученные экспериментально.…”
Section: анализ литературных данных и постановка задачи исследованияunclassified
“…При расчетах и исследованиях характеристик ступеней осевого компрессора в настоящее время используют аэродинамические характеристики компрессорных решеток, которые позволяют с достаточной степенью достоверности анализировать процессы, протекающие в лопаточных венцах ступеней осевого компрессора. В работе [9] приведены аэродинамические характеристики решеток, полученные экспериментально.…”
Section: анализ литературных данных и постановка задачи исследованияunclassified
“…The scale of flue gas turbine is mainly caused by the properties of the catalyst [1][2][3]. Some types of fresh catalysts contain a lot of fine particles and at the same time,a lot of fine particles emerges during the operating process.…”
Section: Main Problems Of the Flue Gas Turbine In Fcc Unitmentioning
confidence: 99%
“…For example, Chen et al. 27 reported that the optional range of bowing parameters would be narrowed by the increasing turning angle. Tan et al.…”
Section: Introductionmentioning
confidence: 99%